Extrusion-state microalloyed magnesium alloy with aging performance and preparation method of extrusion-state microalloyed magnesium alloy
By adopting low alloy element content and high-speed extrusion technology in magnesium alloys, combined with subsequent aging heat treatment, the problem of insufficient mechanical properties of magnesium alloys is solved, and significant mechanical properties are improved and plasticity is maintained.
Patent Information
- Application Number
- CN202411424231.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-25
AI Technical Summary
The application of magnesium alloys in the engineering field is limited by their lower strength and poor plasticity. It is difficult for the prior art to improve the mechanical properties of magnesium alloys while controlling the amount of alloy elements.
A magnesium alloy with low alloy element content is used to produce grain refinement through high-speed extrusion, and subsequent aging heat treatment is carried out to significantly enhance its mechanical properties.
At a lower alloy element addition amount, the mechanical properties of magnesium alloys are significantly improved, including the improvement of hardness and tensile strength, while maintaining the plasticity of the material.
Smart Images

Figure CN119506629A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnesium alloy preparation, and in particular relates to an extruded microalloyed magnesium alloy with aging performance and a preparation method thereof. Background Art
[0002] Magnesium alloy is the lightest structural material with great application prospects. It can be used in aerospace, new energy, medical equipment, electronic devices and other fields. However, the low strength and poor plasticity of magnesium alloy restrict its application in the engineering field. Therefore, using simple and effective processing methods to improve the mechanical properties of the alloy is an important issue that needs to be solved.
[0003] The alloy can improve the microstructure and mechanical properties of the alloy while effectively refining the grains through reasonable plastic deformation. And by adding different kinds of alloying elements, different kinds of precipitate phases are formed inside the alloy through subsequent heat treatment, so as to improve the performance of the alloy. If a higher density of precipitate phases is to be produced, a higher content of alloying elements must be added, but too much alloying elements will make the plastic processing process difficult, the cost will be higher, and it will be difficult to promote and use. It is necessary to control the addition amount of alloying elements at a lower level so that the magnesium alloy can be easily deformed and the mechanical properties of the alloy can be further improved through subsequent heat treatment. Therefore, it is very necessary to develop an extruded microalloyed magnesium alloy with aging properties in actual production applications. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to propose a magnesium alloy composition and process design with a low alloying degree but significantly enhanced mechanical properties through aging heat treatment. The magnesium alloy material contains a low alloying element content, produces grain refinement through high-speed extrusion, and can further improve the mechanical properties of the material through subsequent aging treatment.
[0005] In order to solve the above-mentioned technical problems, this application provides the following technical solutions: The present invention provides a method for preparing an extruded microalloyed magnesium alloy with aging performance, comprising the following steps: S1: magnesium, zinc, aluminum, magnesium-calcium master alloy and magnesium-manganese master alloy are weighed and smelted at 680-700° C. in a protective atmosphere to obtain alloy liquid; in terms of weight fraction, the alloy liquid contains 0.11% calcium, 0.48-0.49% manganese, 0.99-1.04% aluminum, 1.09-1.59% zinc, and the rest is magnesium and unavoidable impurities; S2: casting the alloy liquid under a protective atmosphere and cooling it to room temperature (25±5°C); S3: preheating the sample cooled to room temperature in step S2 at 320-350°C for 0.5-1.5 h and then placing it into a mold preheated to 280-300°C for extrusion; S4: cutting the sample extruded in step S2, subjecting it to aging treatment at 175-225° C. for 0.5-16 h and then water quenching to obtain the extruded microalloyed magnesium alloy with aging properties.
[0006] Preferably, in step S1, after high-temperature smelting, the smelt is left to stand, exhausted and slag removed.
[0007] Furthermore, the standing time is 10 min.
[0008] Preferably, in step S1, the content of unavoidable impurities does not exceed 0.05%.
[0009] Preferably, in step S2, casting is performed in a mold preheated to 200-250°C.
[0010] Preferably, in steps S1 and S2, the protective atmosphere is argon.
[0011] Preferably, in step S3, the oxide scale on the surface of the sample is polished before preheating.
[0012] Preferably, in step S3, the extrusion device and the extrusion container are preheated to 280-300° C. before extrusion.
[0013] Preferably, in step S3, during extrusion, the extrusion temperature is 250-350° C., the extrusion ratio is 18-35:1, and the extrusion speed is 6-24 m / min.
[0014] Specifically, the method for preparing the extruded microalloyed magnesium alloy sheet with aging performance mainly comprises the following steps: (1) Pure magnesium (99.99%), pure zinc (99.99%), pure aluminum (99.99%), magnesium-calcium master alloy, and magnesium-manganese master alloy are weighed in proportion, and each raw material is sequentially added into a high-temperature melting furnace at 680-700°C under the protection of an argon atmosphere; (2) Blow high-purity argon gas into the furnace and let it stand for 10 minutes. After all the raw materials are melted, exhaust gas and remove slag to obtain alloy liquid; (3) pouring the alloy liquid obtained in step (2) into a mold preheated to 200-250° C. under an argon protection atmosphere; (4) After cooling, take out the sample obtained in step (3) from the mold and place it at room temperature; (5) Grinding off the oxide scale on the surface of the sample in step (4) with an angle grinder, and then placing the as-cast magnesium alloy sample in a high-temperature furnace at 320-350° C. and heating it for 0.5-1.5 h for preheating treatment; (6) Preheat the extrusion die and extrusion barrel to 280-300°C; (7) Place the sample preheated in (5) into the mold preheated in (6); (8) Place the material, set the program, the extrusion temperature is 250-350℃, the extrusion ratio is 18-35:1, the extrusion speed is 6-24m / min, and start extrusion; (9) Cutting the extruded sheet in (8) into suitable sizes; (10) The samples cut in (9) are placed in a heat treatment furnace at 175, 200, and 225°C for aging heat treatment for 0.5-16 h. After the aging treatment, the samples are placed in water for water quenching.
[0015] The present invention also provides an extruded microalloyed magnesium alloy with aging performance prepared by the above preparation method.
[0016] The magnesium alloy has the following elements in percentage by mass: 0.11% calcium, 0.48-0.49% manganese, 0.99-1.04% aluminum, 1.09-1.59% zinc, and the remainder being magnesium and inevitable impurities, wherein the content of inevitable impurities does not exceed 0.05% by mass.
[0017] Studies have shown that magnesium alloys can achieve precipitation strengthening through different heat treatment methods such as T4, T5, and T6. Among them, the T5 heat treatment does not have a high-temperature solid solution stage and only performs artificial aging at low temperatures. It will not cause the alloy grains to coarsen. While retaining fine grains, aging treatment can be used to generate precipitation phases in the alloy, further improving the mechanical properties of the alloy.
[0018] Adding different types of alloying elements to magnesium alloys will cause the alloys to generate different types of precipitation phases during the aging process, which can improve the precipitation strengthening ability of the alloys. A large number of research results have shown that Mg-Al-Ca-Mn series magnesium alloys are low in cost and have good room temperature performance, making them a magnesium alloy series with great development prospects. The solid solubility of Zn element in magnesium alloys can reach up to 6.2%, and the addition of Zn element can increase the solubility of Al element in magnesium alloys, laying the foundation for subsequent aging precipitation. Therefore, the Zn element added to the Mg-Al-Ca-Mn series alloy can further improve the mechanical properties of the alloy on the original basis, and the technical solution of the present invention effectively improves the aging performance of the product.
[0019] The technical solution of the present invention has the following advantages over the prior art: (1) The content of the added elements selected by the present invention is low and no rare earth elements are used. The deformation process can be carried out at a high extrusion speed without defects, which improves the market competitiveness. It is safe to use without pollution and harm to the human body and the environment. The alloy elements used are extremely common and easy to obtain, which reduces the industrial production process. After being put on the market, it is also easy to recycle and will not cause polluting industrial waste; (2) Compared with the traditional cast magnesium alloy, the microalloyed extruded magnesium alloy of the present invention can be deformed at a higher extrusion speed without cracking and other defects, and can significantly refine the grains. At the same time, the high temperature and deformation treatment during the extrusion process can also eliminate some second phases with higher solid solution temperatures, preparing for subsequent aging treatment; (3) The entire processing process of the present invention, from alloy casting to extrusion deformation to aging heat treatment, is extremely simple and convenient, and is easy to promote and apply in industrial production; (4) It is difficult to obtain significant aging properties by adding relatively low content of alloying elements in magnesium alloys. However, the present invention can obtain significant aging properties by adding relatively low content of alloying elements and performing relatively simple deformation treatment and aging heat treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the grains of the magnesium alloy material obtained in Example 1 of the present invention.
[0021] Figure 2 This is a hardness discount statistical chart of the magnesium alloy material obtained in Example 1 of the present invention.
[0022] Figure 3 This is the stress-strain curve of the magnesium alloy material obtained in Example 1 of the present invention.
[0023] Figure 4 This is a SEM image of the grains of the magnesium alloy material obtained in Example 2 of the present invention.
[0024] Figure 5 This is a hardness discount statistical chart of the magnesium alloy material obtained in Example 2 of the present invention.
[0025] Figure 6 This is the stress-strain curve of the magnesium alloy material obtained in Example 2 of the present invention.
[0026] Figure 7 This is the BSE diagram of the magnesium alloy material obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention. Example 1
[0028] The microalloyed magnesium alloy prepared in this embodiment contains the following element components: 0.99wt% aluminum, 0.11wt% calcium, 0.48wt% manganese, 1.09wt% zinc, impurities with a content not exceeding 0.05%, and the balance Mg.
[0029] The preparation process is: (1) Pure magnesium with a purity greater than 99.99%, pure zinc with a purity greater than 99.99%, pure aluminum with a purity greater than 99.99%, magnesium-calcium master alloy and magnesium-manganese master alloy are weighed in proportion, and are sequentially added into a high-temperature melting furnace at 680-700°C under argon protection, and high-purity argon is blown into the furnace and allowed to stand for 10 minutes. After all the raw materials are melted, exhaust gas is discharged and slag is removed to obtain alloy liquid; (2) The alloy liquid obtained in step (1) is cast into a steel mold preheated to 250° C. under argon protection, and the sample is taken out after cooling and placed at room temperature; (3) Grind off the surface oxide scale of the sample obtained in step (2) with an angle grinder, and then heat the ground as-cast sample in a high-temperature furnace at 350° C. for 1 h to obtain a preheated sample; (4) The as-cast sample preheated in (3) is added to the preheated punch and die and installed in the extrusion barrel, and a layer of lubricating oil is sprayed on the surface of the punch and die. High-speed extrusion is performed at an extrusion temperature of 350° C., an extrusion ratio of 20:1, and an extrusion speed of 24 m / min to obtain the ageable magnesium alloy sheet after extrusion; wherein the temperature of the preheated extrusion die and extrusion barrel is 300° C.
[0030] (5) The magnesium alloy sheet prepared in (4) was cut into samples of appropriate sizes and placed in a heat treatment furnace at 175, 200, and 225°C for aging heat treatment for 0.5, 1, 2, 4, 8, and 16 h, respectively. After the aging treatment, the samples were placed in water for water quenching. Example 2
[0031] The microalloyed magnesium alloy prepared in this embodiment contains the following element components: 1.04wt% aluminum, 0.11wt% calcium, 0.49wt% manganese, 1.59wt% zinc, impurities with a content not exceeding 0.05%, and the balance Mg.
[0032] The preparation process is: (1) Pure magnesium with a purity greater than 99.99%, pure zinc with a purity greater than 99.99%, pure aluminum with a purity greater than 99.99%, magnesium-calcium master alloy and magnesium-manganese master alloy are weighed in proportion, and are sequentially added into a high-temperature melting furnace at 680-700°C under argon protection, and high-purity argon is blown into the furnace and allowed to stand for 10 minutes. After all the raw materials are melted, exhaust gas is discharged and slag is removed to obtain alloy liquid; (2) The alloy liquid obtained in step (1) is cast into a steel mold preheated to 250° C. under argon protection, and the sample is taken out after cooling and placed at room temperature; (3) Grind off the surface oxide scale of the sample obtained in step (2) with an angle grinder, and then heat the ground as-cast sample in a high-temperature furnace at 350° C. for 1 h to obtain a preheated sample; (4) The as-cast sample preheated in (3) is added to the preheated punch and die and installed in the extrusion barrel, and a layer of lubricating oil is sprayed on the surface of the punch and die. High-speed extrusion is performed at an extrusion temperature of 350° C., an extrusion ratio of 20:1, and an extrusion speed of 24 m / min to obtain the microalloyed magnesium alloy. The temperature of the preheated extrusion die and extrusion barrel is 300° C.
[0033] (5) The magnesium alloy sheet prepared in (4) is cut into samples of appropriate sizes and placed in a heat treatment furnace at 175°C, 200°C, and 225°C for aging heat treatment for 0.5, 1, 2, 4, 8, and 16 h, respectively. After the aging treatment, the sample is placed in water for water quenching.
[0034] Effect evaluation 1
[0035] The microstructure of the magnesium alloy sheet obtained in Example 1 was observed. Figure 1 As shown, it can be found that after high-speed extrusion, the grains of the material are significantly refined, and the crystal structure does not change after refinement.
[0036] The mechanical properties of the magnesium alloy were tested at room temperature. Figure 2 As shown in the figure, the test found that the hardness of the extruded plate obtained by extruding the cast sample without aging treatment was 63.5HV. When aged at 175℃, the peak aging time and hardness were 0.5h and 66.5HV respectively; the peak aging time and hardness at 200℃ were 0.5h and 63.7HV respectively; the peak aging time and hardness at 225℃ were 1h and 60.7HV respectively. Tensile tests were carried out on the peak aging samples at three temperatures, and the test results are shown in the figure below. Figure 3As shown, the yield strength of the extruded sheet is 193.7MPa, the tensile strength is 243.72MPa, and the elongation is 22.8%; the yield strength at 175℃ peak aging is 201.7MPa, the tensile strength is 257.9MPa, and the elongation is 15.7%; the yield strength at 200℃ peak aging is 206.8MPa, the tensile strength is 264.6MPa, and the elongation is 16.5%; the yield strength at 225℃ peak aging is 195.4MPa, the tensile strength is 262.6MPa, and the elongation is 19.7%.
[0037] Effect evaluation 2
[0038] The microstructure of the magnesium alloy sheet obtained in Example 2 was observed. Figure 4 As shown, it can be found that after high-speed extrusion, the grains of the material are significantly refined, and the crystal structure does not change after refinement.
[0039] The mechanical properties of the magnesium alloy were tested at room temperature. Figure 5 As shown in the figure, the test found that the hardness of the extruded plate obtained by extruding the cast sample without aging treatment was 63.5HV. When aged at 175℃, the peak aging time and hardness were 0.5h and 65.5HV respectively; the peak aging time and hardness at 200℃ were 0.5h and 64.7HV respectively; the peak aging time and hardness at 225℃ were 0.5h and 62.8HV respectively. Tensile tests were carried out on the peak aging samples at three temperatures, and the test results are shown in the figure below. Figure 6 As shown, the yield strength of the extruded sheet is 152.2MPa, the tensile strength is 224.1MPa, and the elongation is 22.5%; the yield strength after aging at 175°C peak is 187.2MPa, the tensile strength is 252.1MPa, and the elongation is 20.4%; the yield strength after aging at 200°C peak is 186.5MPa, the tensile strength is 258.5MPa, and the elongation is 18.3%; the yield strength after aging at 225°C peak is 182.5MPa, the tensile strength is 251MPa, and the elongation is 17.1%. After the extruded magnesium alloy of Example 2 is treated at 175°C peak, the yield and tensile strength of the magnesium alloy are effectively improved, but the elongation of the magnesium alloy does not decrease significantly. Figure 7 This is a high-magnification backscattered electron (BSE) image of a magnesium alloy in the peak-aged state at 175°C. It can be clearly seen from the image that there is a high-density nanoscale precipitate phase inside the magnesium alloy.
[0040] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing an extruded microalloyed magnesium alloy having aging properties, characterized in that: The steps include: S1: magnesium, zinc, aluminum, magnesium-calcium master alloy and magnesium-manganese master alloy are weighed and smelted at 680-700° C. in a protective atmosphere to obtain alloy liquid; in terms of weight fraction, the alloy liquid contains 0.11% calcium, 0.48-0.49% manganese, 0.99-1.04% aluminum, 1.09-1.59% zinc, and the rest is magnesium and unavoidable impurities; S2: casting the alloy liquid under a protective atmosphere and cooling it to room temperature; S3: preheating the sample cooled to room temperature in step S2 at 320-350°C for 0.5-1.5 h and then placing it into a mold preheated to 280-300°C for extrusion; S4: cutting the sample extruded in step S2, subjecting it to aging treatment at 175-225° C. for 0.5-16 h and then water quenching to obtain the extruded microalloyed magnesium alloy with aging properties.
2. The preparation method according to claim 1, characterized in that In the step S1, after high-temperature smelting, the smelt is left to stand, exhausted, and slag removed.
3. The preparation method according to claim 3, characterized in that: The standing time is 10 min.
4. The preparation method according to claim 1, characterized in that: In the step S1, the content of unavoidable impurities does not exceed 0.05%.
5. The preparation method according to claim 1, characterized in that: In the step S2, casting is performed in a mold preheated to 200-250°C.
6. The preparation method according to claim 1, characterized in that: In the steps S1 and S2, the protective atmosphere is argon.
7. The preparation method according to claim 1, characterized in that: In the step S3, the oxide scale on the surface of the sample is polished before preheating.
8. The preparation method according to claim 1, characterized in that: In step S3, the extrusion device and the extrusion container are preheated to 280-300° C. before extrusion.
9. The preparation method according to claim 1, characterized in that: In the step S3, during extrusion, the extrusion temperature is 250-350° C., the extrusion ratio is 18-35:1, and the extrusion speed is 6-24 m / min.
10. An extruded microalloyed magnesium alloy with aging properties prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
A low-cost, low-alloyed, high-strength, non-heat-treated high-speed extrusion magnesium alloy and a preparation method thereof
CN122669276A